2017
DOI: 10.1093/mnras/stx2596
|View full text |Cite
|
Sign up to set email alerts
|

A plane of high-velocity galaxies across the Local Group

Abstract: We recently showed that several Local Group (LG) galaxies have much higher radial velocities (RVs) than predicted by a 3D dynamical model of the standard cosmological paradigm. Here, we show that 6 of these 7 galaxies define a thin plane with root mean square thickness of only 101 kpc despite a widest extent of nearly 3 Mpc, much larger than the conventional virial radius of the Milky Way (MW) or M31. This plane passes within ∼ 70 kpc of the MW-M31 barycentre and is oriented so the MW-M31 line is inclined by 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 137 publications
(205 reference statements)
2
57
0
Order By: Relevance
“…For M31, the equivalent quantity is 6.5 × 10 −6 . As discussed in Section 4.4, we expect the MW-M31 orbital plane to align with the plane of high-velocity galaxies discovered by Banik & Zhao (2018b). sense in which the HVGs rotate within their preferred plane, we thus add an extra contribution to the model χ 2 of…”
Section: Alignment With the High-velocity Galaxy Planementioning
confidence: 99%
See 2 more Smart Citations
“…For M31, the equivalent quantity is 6.5 × 10 −6 . As discussed in Section 4.4, we expect the MW-M31 orbital plane to align with the plane of high-velocity galaxies discovered by Banik & Zhao (2018b). sense in which the HVGs rotate within their preferred plane, we thus add an extra contribution to the model χ 2 of…”
Section: Alignment With the High-velocity Galaxy Planementioning
confidence: 99%
“…For M31, we use 21.2 kpc radially and 15.9 kpc vertically. Our plane-fitting procedure is similar to that used in section 5.1 of Banik & Zhao (2018b) but also considers the unequal statistical weights of the particles and applies outlier rejection with a threshold of 2.58σ, corresponding to the 99% confidence interval of a Gaussian distribution. As rejecting outliers reduces the root mean square (rms) plane thickness, we repeat the procedure iteratively until the algorithm no longer finds any outliers.…”
Section: Disk Orientationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this has led to several problems (Kroupa 2012(Kroupa , 2015. In the Local Group, the most serious are the existence of satellite galaxy planes (Pawlowski 2018) and high-velocity dwarfs (Banik & Zhao 2018c). Both problems are rather immune to baryonic physics because they involve length scales of several hundred kpc and relate to the motion of galaxies as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach causes tension with observational data, in particular the apparent absence of dynamical friction expected to arise between the postulated massive and extended dark matter halos (Angus et al 2011;Kroupa 2012Kroupa , 2015Oehm et al 2017). Another problem is that several Local Group dwarf galaxies have anomalously high radial velocities compared to a detailed three-dimensional timing argument calculation (Peebles 2017; Banik & Zhao 2018b). The latter authors showed that these dwarfs are more naturally explained in MOND due to its implication that there was a past close flyby between the Milky Way and Andromeda galaxies ≈ 8 Gyr ago (Zhao et al 2013;Bílek et al 2018;Banik et al 2018).…”
Section: Introductionmentioning
confidence: 99%